Performance and economic assessment of enriched gadolinia burnable absorbers. (July 2021) - Bolukbasi, M.J.; Middleburgh, S.C.; Dahlfors, M.; Lee, W.E.
Abstract: As a burnable absorber, gadolinium oxide (Gd2 O3 ) is widely used in light water reactors due to the high neutron absorption cross section of several gadolinium isotopes and its good solid solubility in UO2 . However, some isotopes of natural Gd cause residual reactivity suppression, while some are not efficient neutron absorbers, reducing the efficiency of the burnable absorber when implemented. In this study, fuel assemblies utilizing gadolinium oxide enriched with 157 Gd isotope were modelled using Monte Carlo particle transport methods and compared to fuel with a natural Gd based absorber. Reactivity gains were examined over the life of the assembly utilizing 157 Gd-enriched absorber as compared to natural gadolinia. A preliminary economic evaluation is also made to assess the commercial benefits of using 157 Gd-enriched burnable absorber. Use of enriched gadolinium oxide is shown to eliminate residual reactivity caused by natural gadolinium oxide, and similar reactivity properties (and therefore criticality margins) can be achieved with less burnable absorber in the fuel. The financial cost of incorporating enriched Gd isotopes into nuclear fuel has also been estimated.